Upaya Meningkatkan Proses Pembelajaran Passing Bawah Bola Voli Kelas XI GP SMK Negeri 2 Karang Baru melalui Pendekatan Teaching Games For Understanding (TGFU) Tahun 2022 - Ahmad Faisal (Multiverse: Open Multidisciplinary Journal, 2022)
The background of this research is the inappropriate use of volleyball teaching methods, which causes students to be inactive and less interested in learning volleyball. This study aims to determine the learning process of volleyball underhand passing through the Teaching Games for Understanding (TGfU) approach in class XI GP SMK Negeri 2 Karang Baru. The subjects of this research were class XI GP students at SMK Negeri 2 Karang Baru, totaling 22 students. This research is a class action research (Classroom Action Research) which is carried out collaboratively and participatively. This study uses an instrument, namely, observation sheets for teachers and students. This study uses quantitative data analysis. The results showed that the Teaching Games for Understanding (TGfU) approach could improve the passing learning process under class XI GP SMK Negeri 2 Karang Baru. The results of this classroom action research show that (1) By using the Teaching Games for Understanding (TGfU) approach students become more active, happy and interested in participating in volleyball learning, (2) The learning outcomes achieved by students increase with a class average score of 76, 5 % (Very Good) and the results of observations of student activity with a total score of 9 (Good).